Hubungan Self-Regulated Learning dengan Prestasi Belajar Matematika Siswa Kelas XI IPS SMA Adabiah Kota Padang - Septiani, Maidatul; Nastasia, Krisnova; Kurniawan, Harri (LITERATUS, 2024)
In this era, human resources are very important. This can be developed through educational models, especially in the field of mathematics. Math is essential for problem solving and decision making in any environment. In fact, many students still fail in math. This makes this research intended to determine the correlation of Self Regulated Learning with Mathematics Learning Achievement at level XI IPS at SMA Adabiah Kota Padang. Self Regulated Learning is the independent variable, while Learning Achievement is the dependent variable. The instrument is measured through the Self Regulated Learning scale and the mean score of the Mathematics report card. Simple saturated sampling technique was used to select the sample, which was 62 students of XI social studies class of Adabiah High School. Validity and reliability were assessed through Cronbach's Alpha method. The validity coefficient is rxy = 0.326 to rxy = 0.861, the reliability coefficient ? = 0.896. The data obtained is 0.333 on sign. 0.009 which means the acceptance of a hypothesis. This result explains that there is a positive relationship between Self Regulated Learning and Math Learning Achievement for XI IPS at Adabiah High School in Padang City.